Re-writing culture in Taiwan - Shih, Fang-Long.; Thompson, Stuart.; Tremlett, Paul-François. (Asia's transformations., 2009)
Examining issues such as trauma, memory, history, tradition, modernity, post-modernity, and with chapters on nationalism, anthropology, cultural studies, media studies, religion and museum studies, this book offers a comprehensive and critical analysis of contemporary Taiwan.